An Energy Demand Model for the Microscopic Simulation of Plug-In-Hybrid Vehicles - Ammon, Lorenz; Huber, Bernd; Hübler, Florian; Berndt, Rüdiger; Schellenberg, Sebastian; Schneider, Vitali (Proceedings of the 2016 IEEE Transportation Electrification Conference and Expo (ITEC 2016), 2016)
More and more car manufactures are combining a normal combustion engine and an electric motor to satisfy the standards for CO2 emissions. In order to take advantage of this technology in the most efficient way, for example in companies car fleets, realistic simulation models are required. In this paper, we present an accurate yet computationally inexpensive energy demand model for the microscopic simulation of plug-in hybrid vehicles. Our model mostly consists of a combustion engine, an electric motor and, most importantly, a realistic engine management model. Furthermore, a pragmatic kinematic model as well as a model for recuperation of energy while breaking are provided. Modularly designed, our simulation model allows for simple replacement and adjustment of each module. As input values, our model only requires the vehicle's speed and a set of constant predefined parameters. Consequently, this also enables the model to be easily connected with current sophisticated traffic simulators. We show the correctness of our model regarding the consumption of fuel and electric energy using comprehensive real-world experiments.
Keywords: Mathematical model; Object oriented modeling; Electromobility; Plug-in Hybrid Electric Vehicle; Simulation

An Integrated Model-driven Framework for Simulation, Analysis, and Testing Based on OMG Standards - Schneider, Vitali; Deitsch, Anna; German, Reinhard (10th International Conference on Performance Evaluation Methodologies and Tools, 2016)
Keywords: Test-driven Agile Simulation; Model-driven Engineering; Performance analysis; UML; Model-driven Testing

An Integrated Model-driven Framework for Simulation, Analysis, and Testing Based on OMG Standards - Schneider, Vitali; Deitsch, Anna; German, Reinhard (Proceedings of the 10th International Conference on Performance Evaluation Methodologies and Tools (ValueTools '16), 2017)
Model-driven engineering techniques are becoming increasingly popular for cost-effective and highly productive software development. Particularly, approaches and tools based on the standards provided by the Object Management Group (OMG), first of all on its famous Unified Modeling Language (UML), are already widespread throughout both the industry and the research community. Following this trend, the approach for Test-driven Agile Simulation (TAS) combines model-driven engineering, simulation, and testing techniques, based on OMG standards, to allow for advanced performance analysis and validation at early design stages. Among others, by deriving executable simulations from a system model and test specifications, this approach provides a cheap and agile technique for quantitative assessments and quality assurance of the system under design. In this paper, we present the current state of the SimTAny framework that provides a versatile, integrated, and standard-based tool chain to support the TAS approach. In particular, SimTAny facilitates the creation of model specifications, based on UML and several standardized profiles like SysML, MARTE, and UTP, the automated transformation to executable simulations, as well as testing and analysis activities. We demonstrate the main features of the SimTAny framework and illustrate the application of TAS on an example monocular vision system for the autonomous approach and landing that uses a low-budget micro aerial vehicle syste
UnivIS-Import:2017-01-09:Pub.2016.tech.IMMD.IMMD7.aninte_6
Keywords: model-driven engineering; model-driven testing; performance analysis; test-driven agile simulation; UML

Combined Simulation and Testing Based on Standard UML Models - Schneider, Vitali; Deitsch, Anna; Dulz, Winfried; German, Reinhard (Principles of Performance and Reliability Modeling and Evaluation, 2016)

How to Avoid Model Interferences for Test-driven Agile Simulation based on Standardized UML Profiles - Schneider, Vitali; Yupatova, Anna; Dulz, Winfried; German, Reinhard (Proceedings of the Symposium on Theory of Modeling and Simulation - DEVS Integrative (DEVS '14), 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.howtoa
Keywords: GRK-1773

Integration of Test-Driven Agile Simulation Approach in Service-Oriented Tool Environment - Schneider, Vitali; German, Reinhard (Proceedings of the 46th Annual Simulation Symposium (ANSS '13), 2013)
The approach of test-driven agile simulation combines model-based simulation and testing techniques to achieve an improved overall quality during the development process. It intends to provide a cheap and agile technique to validate the models in several iteration steps during early engineering phases. Designated phases of this process can be automated and supported by specialized tools. Originally, the suggested tools have been integrated in one framework, which was only accessible on a single machine. In this paper we show how this approach could be integrated in a distributed, service-oriented tool environment to profit by the advantages of the service-based architecture, such as higher accessibility, interoperability and extensibility. Towards this goal, we specify loosely coupled services for validation, transformation and simulation of models, which may exchange data through formally defined interfaces. Based on common technologies and standards these services are integrated in a heterogeneous development environment to support the whole development lifecycle.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD7.integr
Keywords: Service-oriented computing and simulation; Simulation tools and environments; Test-driven agile simulation; Verification and validation

Merging OMG Standards in a General Modeling, Transformation, and Simulation Framework - Schneider, Vitali; Yupatova, Anna; Dulz, Winfried; German, Reinhard (Proceedings of the 8th International Conference on Simulation Tools and Techniques (SIMUTools '15), 2015)
Keywords: MARTE; MOF2T; OMG; SysML; UML; UTP; model-driven engineering; model-driven testing; test-driven agile simulation

Model-Based System Design and Evaluation of Image Processing Architectures with SimTAny Framework - Deitsch, Anna; Schneider, Vitali (Measurement, Modelling and Evaluation of Computing Systems, 2018)
Becoming a ubiquitous part of a huge number of various applications, image processing algorithms and underling architectures have to meet many different requirements. Some have real-time performance constraints combined with demands on efficient implementation for limited or various hardware resources. This poses particular challenges for design, implementation, and evaluation of efficient image processing systems. In this paper, we present a model-based approach to address these issues using our framework SimTAny. Founded on the standard modeling language UML, we propose the UML Image Proccessing Language (UIPL) to facilitate expressing image processing application algorithms directly in UML, which is especially beneficial for rapid modeling. With the help of SimTAny, such design models can be simulated in order to investigate the performance of a modeled system, to determine optimal design solutions, and to validate the required properties. We extend SimTAny to enable the generation of efficient implementation code of image processing algorithms for different target architectures. The code generated is then directly integrated in the simulation environment to increase the accuracy of our performance evaluations.<br
Keywords: Model driven engineering; UML; SysML; MARTE; Image processing applications; High-level synthesis

Simulating the Energy Management on Smartphones Using Hybrid Modeling Techniques - Alagöz, Ibrahim; Löffler, Christoffer; Schneider, Vitali; German, Reinhard (Proceedings of the 17th International GI/ITG Conference, MMB & DFT 2014, 2014)
With the global growth of the market for smartphones new business ideas and applications are developed continuously. These often utilize the resources of a mobile device to a considerable extent and reach the limits of these. In this work we focus on the simulation of an on-demand music service on a modern smartphone. Our simulation model includes higher level descriptions of the necessary hardware components' behavior and their energy consumption. Thereby, the detailed simulation of battery plays a key role in the project. With this simulation study we find optimal parameters for the users of the examined application to maximize playback time, improve its battery life and reduce costly data transmissions. © 2014 Springer International Publishing.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.simula
Keywords: battery lifetime; energy management; kinetic battery model; simulation study; smartphone; streaming music on-demand

Test-Driven Agile Simulation for Design of Image Processing Systems - Yupatova, Anna; Schneider, Vitali; Dulz, Winfried; German, Reinhard (The Sixth International Conference on Advances in System Testing and Validation Lifecycle (VALID 2014), 2014)
Image processing systems are characterized by very high computational demand caused by large amounts of data, short response times, and the complexity of image processing tasks. For these reasons, specialized hardware solutions based on multiple processing cores, complex interconnects, or custom hardware elements are used for image processing. Due to the complexity of the computational tasks, the complexity of the specialized hardware solutions is continuously increasing. Therefore, new design techniques that reduce the risk of lacks in the system design or of expensive design-to-implementation iterations are desirable. Test-driven Agile Simulation (TAS) is a generalpurpose approach that combines novel model-based simulation and testing techniques to achieve an improved overall quality for the development process. In this paper, we present an application and extension of the TAS approach for the efficient design process of image processing systems.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.testdr
Keywords: GRK-1773

Towards an Efficient High-Level Modeling of Heterogeneous Image Processing Systems - Deitsch, Anna; Schneider, Vitali; Kane, Jennifer; Dulz, Winfried; German, Reinhard (Proceedings of the Symposium on Theory of Modeling & Simulation - DEVS Integrative (DEVS '16), 2016)
Keywords: TAS; image processing systems; marte; model-based engineering; sysml; test-driven agile simulation; uml; utp

VeriTAS - A Versatile Modeling Environment for Test-driven Agile Simulation - Djanatliev, Anatoli; Dulz, Winfried; German, Reinhard; Schneider, Vitali (Proceedings of the 2011 Winter Simulation Conference (WSC '11), 2011)
An approach is presented in which both simulation and testing based on UML are combined in one framework to achieve an improved overall quality. System models are specified by UML diagrams, and are then mapped on C++-code and executed in the OMNeT++ network simulation framework. State-space oriented test models are defined independently from this to express requirements by selected system usages. From these test models it is possible to generate test cases and to execute them on the simulation code level. By adding Markov chain usage profiles to the test model it is possible to apply statistical test case generation as well. Altogether this allows to validate both kinds of models systematically and iteratively during the development cycle. The methodology is realized by combining appropriate tools and new software components based on the Eclipse RCP. The approach is also well suited for software engineering because standard modeling languages are used. © 2011 IEE
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD7.verita
Keywords: Test-driven Agile Simulation; Validation and Verification